Characteristics of Microbes Most Likely to Cause Pandemics and Global Catastrophes - Adalja, Amesh A. (Global Catastrophic Biological Risks, 2019)
Predicting which pathogen will confer the highest global catastrophic biological risk (GCBR) of a pandemic is a difficult task. Many approaches are retrospective and premised on prior pandemics; however, such an approach may fail to appreciate novel threats that do not have exact historical precedent. In this paper, based on a study and project we undertook, a new paradigm for pandemic preparedness is presented. This paradigm seeks to root pandemic risk in actual attributes possessed by specific classes of microbial organisms and leads to specific recommendations to augment preparedness activities.